Le rôle d’al-Andalus dans l’introduction du malikisme au Maghreb extrême : l’exemple de Fès (ive/xe siècle) - Aurélien Montel (Mélanges de la Casa de Velázquez, 2023)
Since the 5th/11th century, the city of Fez (in present-day Morocco) has been holding a major role within the scholars’ networks of the Islamic West, especially as an important place of transmission of the Mālikī Sunnism. However, little is known about the establishment of this school of thought in Fez. Opinions on that matter differ amongst medieval authors. Following the biographical literature (ṭabaqāt), the spread of Mālikī Sunnism in the city can be attributed to the influence of great Sunnite ulama, such as Darrās b. Ismāʽīl (d. 357/967), a Fassi ulama who spent time in the Iberian Peninsula. For their part, chroniclers see it as a result of the imperial policy led in the Far Maghrib by the Umayyad caliphs of Cordoba. In fact, those two components combined, highlighting the important function of al-Andalus in the introduction, the establishment and the acknowledgement of the mālikī maḏhab in Fez.